Specific DNA duplex formation at an artificial lipid bilayer: fluorescence microscopy after Sybr Green I staining - Werz, Emma; Rosemeyer, Helmut (Beilstein Journal of Organic Chemistry, 2014)
The article describes the immobilization of different probe oligonucleotides (4, 7, 10) carrying each a racemic mixture of 2,3-bis(hexadecyloxy)propan-1-ol (1a) at the 5’-terminus on a stable artificial lipid bilayer composed of 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphoethanolamine (POPE) and 1-palmitoyl-2-oleoyl-sn-glycero-3-phosphocholine (POPC). The bilayer separates two compartments (cis/trans channel) of an optical transparent microfluidic sample carrier with perfusion capabilities. Injection of unlabeled target DNA sequences (6, 8, or 9), differing in sequence and length, leads in the case of complementarity to the formation of stable DNA duplexes at the bilayer surface. This could be verified by Sybr Green I double strand staining, followed by incubation periods and thorough perfusions, and was visualized by single molecule fluorescence spectroscopy and microscopy. The different bilayer-immobilized complexes consisting of various DNA duplexes and the fluorescent dye were studied with respect to the kinetics of their formation as well as to their stability against perfusion.
Keywords: artificial lipid bilayers; lipo-oligonucleotide duplexes; nucleic acids; Sybr Green I

(untitled) - Roskoski, R., Jr (Biochem. Biophys. Res. Commun., 2003)

(untitled) - Dumelin, C. E.; Chen, Y.; Leconte, A. M.; Chen, Y. G.; Liu, D. R. (Nat. Chem. Biol., 2012)

(untitled) - Pokholenko, O.; Gissot, A.; Vialet, B.; Bathany, K.; Thiéry, A.; Barthélémy, P. (J. Mater. Chem. B, 2013)

(untitled) - Gissot, A.; Camplo, M.; Grinstaff, M. W.; Barthélémy, P. (Org. Biomol. Chem., 2008)

(untitled) - Langecker, M.; Arnaut, V.; List, J.; Simmel, F. C. (Acc. Chem. Res., 2014)

(untitled) - Taib, N.; Aimé, A.; Houmadi, S.; Castano, S.; Barthélémy, P.; Laguerre, M.; Bestel, I. (Langmuir, 2012)

(untitled) - Desbat, B.; Arazam, N.; Khiati, S.; Tonelli, G.; Neri, W.; Barthélémy, P.; Navailles, L. (Langmuir, 2012)

(untitled) - Loew, M.; Springer, R.; Scolari, S.; Altenbrunn, F.; Seitz, O.; Liebscher, J.; Huster, D.; Herrmann, A.; Arbuzova, A. (J. Am. Chem. Soc., 2010)

(untitled) - Johnson-Buck, A.; Jiang, S.; Yan, H.; Walter, N. G. (ACS Nano, 2014)

(untitled) - Montis, C.; Baglioni, P.; Berti, D. (Soft Matter, 2014)

(untitled) - Bunge, A.; Loew, M.; Pescador, P.; Arbuzova, A.; Brodersen, N.; Kang, J.; Dähne, L.; Liebscher, J.; Herrmann, A.; Stengel, G.; Huster, D. (J. Phys. Chem., 2009)

(untitled) - Peer, D.; Lieberman, J. (Gene Ther., 2011)

(untitled) - Wolfrum, C.; Shi, S.; Jayaprakash, K. N.; Jayaraman, M.; Wang, G.; Pandey, R. K.; Rajeev, K. G.; Nakayama, T.; Charrise, K.; Ndungo, E. M.; Zimmermann, T.; Koteliansky, V.; et al. (Nat. Biotechnol., 2007)

(untitled) - Kurz, A.; Bunge, A.; Windeck, A.-K.; Rost, M.; Flasche, W.; Arbuzova, A.; Strohbach, D.; Müller, S.; Liebscher, J.; Huster, D.; Herrmann, A. (Angew. Chem., Int. Ed., 2006)

(untitled) - Honigmann, A.; Walter, C.; Erdmann, F.; Eggeling, C.; Wagner, R. (Biophys. J., 2010)

U.S. Patent - Rosemeyer, H. (Nucleolipids and use thereof, and devices for nucleic acid analysis, 2011)

Eur. Patent - Rosemeyer, H. (Nucleolipide und deren Verwendung, sowie Vorrichtung zur Nucleinsäureanalytik, 2013)

(untitled) - Rode, A. B.; Endoh, T.; Tateishi-Karimata, H.; Takahashi, S.; Sugimoto, N. (Chem. Commun., 2013)

(untitled) - Werz, E.; Korneev, S.; Montilla-Martinez, M.; Wagner, R.; Hemmler, R.; Walter, C.; Eisfeld, J.; Gall, K.; Rosemeyer, H. (Chem. Biodiversity, 2012)

(untitled) - Zipper, H.; Brunner, H.; Bernhagen, J.; Vitzthum, F. (Nucleic Acids Res., 2004)

Entwicklung analytisch-molekularbiologischer Verfahren zur Konstruktion einer Plasmid-Gendatenbank aus Boden-DNA in Escherichia coli und deren Durchmusterung nach neuen Enzymen für die technische Anwendung - Zipper, H. (University of Stuttgart, 2004)

(untitled) - Dragan, A. I.; Pavlovic, R.; McGivney, J. B.; Casas-Finet, J. R.; Bishop, E. S.; Strouse, R. J.; Schenerman, M. A.; Geddes, C. D. (J. Fluoresc., 2012)

(untitled) - Malecki, E.; Farhat, A.; Bonaterra, G. A.; Röthlein, D.; Wolf, M.; Schmitt, J.; Kinscherf, R.; Rosemeyer, H. (Chem. Biodiversity, 2013)

(untitled) - Farhat, A.; Malecki, E.; Bonaterra, G. A.; Röthlein, D.; Wolf, M.; Schmitt, J.; Rosemeyer, H.; Kinscherf, R. (Chem. Biodiversity, 2014)